2015
DOI: 10.1016/j.cognition.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stability modulates the role of path integration in human navigation

Abstract: Path integration has long been thought of as an obligatory process that automatically updates one's position and orientation during navigation. This has led to the hypotheses that path integration serves as a back-up system in case landmark navigation fails, and a reference system that detects discrepant landmarks. Three experiments tested these hypotheses in humans, using a homing task with a catch-trial paradigm. Contrary to the back-up system hypothesis, when stable landmarks unexpectedly disappeared on cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 50 publications
0
58
0
Order By: Relevance
“…However, other research has cast doubt on the idea that path integration functions as a backup system. Zhao and Warren (2015a) found that participants could not use path integration to perform a simple navigation task after previously visible environmental cues had been unexpectedly removed. On subsequent trials, however, participants were able to use path integration alone, indicating that they changed strategies after learning that environmental cues might not be completely reliable.…”
Section: Discussionmentioning
confidence: 99%
“…However, other research has cast doubt on the idea that path integration functions as a backup system. Zhao and Warren (2015a) found that participants could not use path integration to perform a simple navigation task after previously visible environmental cues had been unexpectedly removed. On subsequent trials, however, participants were able to use path integration alone, indicating that they changed strategies after learning that environmental cues might not be completely reliable.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, path integration is not automatic and continuous, but intermittent and discontinuous. In an environment with stable visual landmarks for piloting, the path integrator actually shuts down, so the navigator is completely disoriented if landmarks unexpectedly vanish (Zhao and Warren, 2015a). Moreover, familiar visual landmarks act to reset the path integrator (both orientation and position) in humans (Mou and Zhang, 2014;Zhang and Mou, 2017;Zhao and Warren, 2015b) as in animals (Etienne et al, 2004;Knierim et al, 1998).…”
Section: Building a Cognitive Graphmentioning
confidence: 99%
“…When there is a large discrepancy between feature and geometric cues, participants should choose between the conflicting cues (Cheng et al, 2007). We speculated that the switch from integration to choice might occur at 90 degrees, based on Ratliff and Newcombe (2008) and also on data on combining or choosing between landmarks and dead reckoning (Zhao & Warren, 2015).…”
Section: Introductionmentioning
confidence: 99%